Judicial Activism dalam Pengujian Konstitusionalitas Undang-Undang Ratifikasi (Judicial Activism in Reviewing the Constitutionality of the Ratification Law) - Dicky Eko Prasetio; Adam Ilyas (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2022)
The review of the ratification law still raises polemics regarding whether or not a ratification law can be constitutionally reviewed at the Constitutional Court. Therefore, this study will examine the position of ratification law related to constitutionality review by the Constitutional Court. The research method used is normative juridical research, with a statutory approach and a conceptual approach. The results of the study indicate that judging from its form and urgency, the ratification law has an equal position with ordinary laws. Hence, the ratification law is part of the phrase “law” which is the object of review by the Constitutional Court. Assessing from the concept of judicial activism, the activeness of judges is needed in reviewing the ratification law based on the concept of the law is non-transferability of law so that the ratification law, which is the result of international agreements, is not “sub-ordinated” to national law. Therefore, the review against the ratification law can be carried out in the Constitutional Court by means of extensive interpretation of the phrase “law” so that it includes not only ordinary laws but also ratification laws. In addition, in future arrangements regarding the review of the ratification law, the Constitutional Court needs to carry out judicial activism, namely a progressive and substantive effort to review the compatibility between the ratification law and the constitution. In practice, this can be done in the future by means of a judicial preview as a legal effort for the Constitutional Court to review the ratification law. AbstrakPengujian undang-undang (UU) ratifikasi selama ini masih menimbulkan polemik terkait boleh atau tidaknya dilakukan constitutional review di Mahkamah Konstitusi (MK). Oleh karena itu, penelitian ini akan mengkaji bagaimana kedudukan UU ratifikasi terkait pengujian konstitusionalitas oleh MK. Metode penelitian yang digunakan adalah metode penelitian yuridis normatif, dengan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian menunjukkan bahwa dilihat dari bentuk dan urgensinya maka UU ratifikasi memiliki kedudukan yang sederajat dengan UU biasa sehingga secara hukum UU ratifikasi merupakan bagian dari frasa “undang-undang” yang merupakan objek pengujian dari MK. Dilihat dari konsep judicial activism, keaktifan hakim diperlukan dalam pengujian UU ratifikasi berdasarkan konsep the law is non transferability of law supaya UU ratifikasi yang merupakan hasil perjanjian internasional tidak bersifat “sub-ordinasi” bagi hukum nasional. Oleh karena itu, pengujian UU ratifikasi dapat dilakukan di MK dengan cara penafsiran secara ekstensif atas frasa “undang-undang” sehingga bukan hanya meliputi UU biasa, namun juga termasuk UU ratifikasi. Selain itu, pengaturan ke depan mengenai pengujian UU ratifikasi maka MK perlu melakukan judicial activism yaitu upaya progresif dan substantif untuk menguji kesesuaian antara UU ratifikasi dengan konstitusi. Hal ini dalam praktiknya, ke depan dapat dilakukan dengan upaya judicial preview sebagai upaya hukumMK menguji UU ratifikasi.